HUBUNGAN FAKTOR MAKROEKONOMI DENGAN PENCADANGAN KERUGIAN PENURUNAN NILAI - Sjahbandi, Hisyam Abdussalam; Ahalik, Ahalik (Unversitas Prof. Dr. Moestopo (Beragama), 2024)
PSAK No. 71 is an adoption of IFRS 9 whose implementation has only been effective since January 1, 2020. PSAK 71 as a new regulation will have an impact on companies in Indonesia, especially on companies listed in the LQ 45 index. Especially in calculating CKPN. PSAK 71 introduces a new method for calculating CKPN, namely forward-looking expected loss. In addition to being forward-looking, this new standard also requires companies to include information from past events and current conditions in the calculation and measurement of expected credit loss (ECL). In the new standard, macroeconomic data is one of the supporting factors in calculating a company's CKPN, because it includes information about future events. This means that the company must prepare CKPN for accounts that have the potential for impairment and include macroeconomic data into the calculation of the company's CKPN. This study aims to examine the relationship of macroeconomic factors to the value of the company's CKPN. The macro factors studied by this researcher are inflation, exchange rate and BI rate. The method used in this research is descriptive quantitative with multiple linear regression data processing. The results of this study were found if the macroeconomic data simultaneously did not have a significant effect on the calculation of the CKPN value.